2022
DOI: 10.3390/app12031541
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve the Acceptance of Autonomous Driving Technology: Effective Elements Identified on the Basis of the Kano Model

Abstract: Innovative sociotechnical change is forthcoming because of autonomous driving; however, only a few studies have focused on the acceptance of this technology, which is not up to social expectation. In this study, we present and validate a research framework on the basis of the Kano model to identify the effective acceptance elements for autonomous driving technology. By collecting and analyzing the survey data of 187 people, it was confirmed that the elements of acceptance for autonomous driving technology can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Women riders' topic preference degree is concentrated in about 0.1 to 0.2, and there are gradient differences in sentiment preference. According to Shin et al, the results are shown in Figure 11 (M.-C. Chen et al, 2021;Shin et al, 2022).…”
Section: Topic-sentiment Preference Analysismentioning
confidence: 93%
“…Women riders' topic preference degree is concentrated in about 0.1 to 0.2, and there are gradient differences in sentiment preference. According to Shin et al, the results are shown in Figure 11 (M.-C. Chen et al, 2021;Shin et al, 2022).…”
Section: Topic-sentiment Preference Analysismentioning
confidence: 93%
“…The Kano model approach has been widely used in various studies. Shin et al used the Kano model to evaluate the service quality and satisfaction of driving products and proposed a framework to improve the future car-driving service experience [23]. Xie et al analyzed the different factors that affect the acceptance of hotel robots through the Kano model approach [24].…”
Section: The Kano Modelmentioning
confidence: 99%
“…We designed a questionnaire using the Kano model to assess the attributes of patients' needs factors. Each factor was linked to a pair of questions (a functional question and a dysfunctional question) [23,32]. Participants could choose from one of five answers (like, must-be, neutral, live with, and dislike) for each question.…”
Section: Questionnaire Based On the Kano Modelmentioning
confidence: 99%